Cement extravasation as a complication for kyphoplasty and vertebroplasty procedure: a retrospective analysis of 171 cases - Sultan Jarrar; Mohammed M. AL Barbarawi; Suleiman S. Daoud; Amer Jaradat; Rand Alkalban; Layan Abu Qayyas; Nadeem B. Alabdallah; Basel W. Khurfan; Ala’ M. Al Barbarawi; Ziad A. Audat (Medicinski glasnik, 2023)
Aim: Kyphoplasty and vertebroplasty are minimally invasive procedures used in bone augmentation following vertebral fractures when conservative management has failed. Cement injection could leak into surrounding structures leading to post-operative sequelae, which could be symptomatic. This study compared the rate and site of cement extravasation in vertebroplasty, kyphoplasty, and a combined approach. The indications, aetiology, and factors influencing results and the effect of screws were considered. Methods: A retrospective descriptive study of 171 patients was conducted between 2009 and 2021. Only 89 patients had available imaging. The site of cement extravasation was evaluated postoperatively by CT-scan and X-ray. Results: There was a statistically significant difference in the prevalence of cement extravasation between kyphoplasty and vertebroplasty procedures (p=0.004). Age and gender had no significant influence on the rate of cement extravasation. Patients who underwent kyphoplasty had the lowest rate of cement extravasation (46.9%) compared to vertebroplasty (85.2%) and the combined approach (69.2%). The most common site of leakage was in perivertebral veins (37.9%). The use of screws did not indicate a greater risk of cement leak (p=0.652). Bone metastases were the aetiology with the highest cement leakage rate (27.5%). Conclusion: The use of kyphoplasty alone or in conjunction with vertebroplasty decreases the risk of cement extravasation and subsequent complications compared to vertebroplasty alone. The use of pedicle screws appears to be safe and was not found to increase the risk of cement extravasation.
Keywords: bone metastases; minimally invasive surgical procedures; postoperative complications; spinal fractures